Solid-phase extraction based sample preparation for the determination of drug and organic pollutant residue - Pule, Bellah Oreeditse (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This thesis presents solid phase extraction (SPE) methodologies based on mixed-mode polymeric sorbents; a mixed mode strong anion exchanger (Agilent SampliQ SAX) and a mixed mode strong cation exchanger (Agilent SampliQ SCX). Furthermore, dispersive-SPE based on a quick, easy, cheap, effective, rugged and safe (QuEChERS) method was assessed for applicability in the determination of drug residues. The mixed-mode polymeric sorbents were evaluated for the simultaneous fractionation of drugs that exhibit diverse polarities with acidic, basic and neutral functionalities in biological matrices (plasma and urine). The polymeric skeleton of these sorbents entails an exchanger group and therefore provides two retention mechanisms, strong cation or anion exchange retention mechanisms with hydrophobic interactions. It was demonstrated that with a sequential elution protocol for sample clean-up analytes were fractionated into acidic, basic and neutral classes. The SAX was employed for analysis of ketoprofen, naproxen (acidic drugs), nortriptyline (basic) and secobarbital (neutral) from urine sample. The SCX was used for fractionating phenobarbital, p-toluamide (acidic), amphetamine, m-toluidine (basic) and acetaminophen (neutral drug) from plasma sample. QuEChERS method was employed for quantitative determination of 16 polycyclic aromatic hydrocarbons (PAHs) from fish fillets and soil; 9 sulfonamides (SAs) from chicken muscles and acrylamide (AA) in cooking oil. The analyte recoveries ranged from 79.6 - 109% with RSDs ranging from 0.06 - 1.9% at three different fortification levels. Good linearity (r2 > 0.9990) was attained for most analytes. The limits of detection and quantification ranged from 0.03 - 0.84 Î¼g/ml and 0.81 - 1.89 Î¼g/ml respectively for analytes in biological samples. LODs and LOQs for analytes in food and environmental samples ranged from 0.02 to 0.39 and 0.25 to 1.30 ng/g respectively.
Keywords: Food contamination; Drugs -- Analysis; Pharmaceutical chemistry; Extraction (Chemistry); Sorbents